Bifunctional Ce1−xEuxO2 (0 ≤ x ≤ 0.3) nanoparticles for photoluminescence and photocatalyst applications: an X-ray absorption spectroscopy study. Issue 44 (26th October 2015) - Sharma, Aditya; Varshney, Mayora; Park, Jaehun; Ha, Tae Kyun; Chae, Keun Hwa; Shin, Hyun Joon
Abstract : Eu dopants in CeO2 leads to advancement in electronic structure, photoluminescence and photocatalyst properties. Abstract : Ce1− x Eu x O2 (0 ≤ x ≤ 0.3) nanoparticles (NPs) were synthesized by the chemical precipitation method. The microstructures and morphology were characterized by synchrotron X-ray diffraction and high resolution transmission electron microscopy. X-ray absorption near edge structure (XANES) spectra at the Eu M5, 4 -edge and atomic-multiplet calculations revealed that Eu 3+ was predominantly present in the CeO2 lattice and Eu 2+ was negligibly present within the entire doping range. The detailed analysis of the Ce M5, 4 -edge and the O K-edge has shown strong dependence of the Ce 3+ /Ce 4+ ratio and oxygen vacancy with Eu content. Extended X-ray absorption fine structure (EXAFS) spectra at the Ce K-edge, along with theoretical fitting, have shown systematic variation in the coordination number, bond length and Debye–Waller factor with Eu doping. A blue shift in the absorption edge was observed which implies a net increase in the charge transfer gap between the O 2p and Ce 4f bands due to the increased number of Ce 3+ ions in the Eu doped samples. The excitation and emission spectra of pure CeO2 NPs did not show any photoluminescence (PL) characteristic; however, Ce1− x Eu x O2 ( x = 0.1–0.3) NPs showed significant improvements in the 4f–4f, 5 D0 – 7 F2 and 5 D0 – 7 F1 transitions induced luminescence properties. Eu doping has two major effects on the electronic structure and optical properties of CeO2 NPs: the first, at an Eu content of 10 mol%, is the formation of Ce 4+ –O–Eu 3+ networks, i.e., Eu 3+ ions substitute the Ce 4+ ions and introduce oxygen vacancies and Ce 3+ ions in the host lattice, which favors the 5 D0 – 7 F2 induced PL properties. The other, at an Eu doping over 10 mol%, is the formation of both Ce 4+ –O–Eu 3+ and Ce 3+ –O–Eu 3+, i.e., Eu 3+ ions not only take substitutional sites of Ce 4+ ions but also replace a fraction of Ce 3+ ions in the CeO2 lattice which favors 5 D0 – 7 F1 induced PL properties. As an application of CeO2 NPs towards the degradation of water pollutants, we demonstrated that the Ce1− x Eu x O2 (0 ≤ x ≤ 0.3) NPs can serve as effective photocatalyst materials towards the degradation of the methyl-orange aqueous pollutant dye under UV light irradiation.